Comparación de técnicas de evaluación multicriterio en sistemas de ayuda a la decisión espacial para la localiación óptima de uso residencial - Lamelas Gracia, María Teresa (Geographicalia, 2014)
The development of spatial decision support systems (SDSS) has greatly assisted efforts for solving the complex landuse conflicts that commonly appear in a sustainable landuse management. In this paper we compare the results obtained by the application of two distinctive landuse suitability analyses to the location of residential land use, applying two different multicriteria analysis techniques. The multicriteria analysis employed has been performed in a raster environment and been used for two objectives, namely for site search and a spatial suitability assessment. During the site search analysis each pixel was considered a potential location alternative. This analysis was performed using a simple additive weighting (SAW) method, which can easily be performed in GIS. A site selection analysis was then performed using the PROMETHEE-2 methodology and using a set of predefined alternatives. The main conclusion from the obtained results is the similarity of the results obtained after applying the different approaches and the necessity of applying stochastic approaches in order to control the uncertainty of the input data.